Oral Microbes Associated with Pulp and Periapical Infections - Bonnis Benny; Varun Raghavan Pillai; Anna Joseph; Jayanthi Pazhani; Vinod Mony (Wolters Kluwer Medknow Publications, 2022)
Intoduction: Endodontic treatment procedures are designed to eradicate infection and prevent germs from infecting or reinfecting the root and/or periapical tissues. As a result, a thorough understanding of the endodontic microbiome is critical to the efficacy of endodontic treatment in diverse types of illness. We conducted a thorough and critical assessment of original research articles that looked into the microbiota of pulp and periapical infections for this study. Primary apical periodontitis, secondary apical periodontitis, and apical abscess are the endodontic diseases included in this study. Materials and Methods: The PRISMA statement and Cochrane criteria for systematic reviews were followed in the preparation of this systematic review's methodology. For works published between 2000 and 2020, a thorough literature search was undertaken independently by two researchers in the PubMed, SCOPUS, and EMBASE databases. We found all of the papers that contained original data on oral microorganisms in pulp and periapical diseases. Anecdotal evidence, case reports, and reviews were excluded from the study. The complete text of 36 articles that satisfied the inclusion criteria were retrieved and reviewed for sample methodology, sequencing strategy, and microbiome makeup. All 36 publications were critically examined independently by three authors, following the Joanna Briggs Institute Reviewer's Manual of 2017. Results: Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria, and Fusobacteria were the most common phyla represented. Conclusion: All infection types are associated with an exceedingly diverse microbiome. These studies together map out an exhaustive chart of the taxa inherent in endodontic infections.